PERCEPTIONS OF FAMILY HURDLES AMONG EMERGING ADULTS: A PRELIMINARY STUDY ABOUT RESILIENCE IN THE INDONESIAN FAMILY - Ediati, Annastasia; Salma, Salma; Kaloeti, Dian Veronika Sakti (Faculty of Psychology, Diponegoro University, 2020)
Family resilience is an essential skill for family members to deal with problems in their families. It is a condition in which a family able to adapt and successfully cope with stress, either now or in the future. Emerging adults are faced with a number of development tasks that focus on career development, independence, and building a family. The study aims to explore to what extent emerging adults in Indonesia interpret the problems in their families and describe their self-efficacies in dealing with these problems. The study participants comprised 1,010 emerging adults (aged 18-25 years old) who studied at various universities in Indonesia. They were approached using a snowball sampling technique. An indigenous psychology approach was used in the study and data were analyzed qualitatively. The results of data analysis showed that emerging adults in Indonesia positively interpreted the problems in their families. In addition, the majority of participants indicated of having self-efficacy towards problem-solving. We applied the sense of coherence concept to explain positive meanings and self-efficacy that have a positive impact on emerging adults in developing into resilient individuals in responding to the challenges of developmental tasks in the transition to adulthood.